Research on Gender and Sexualities in Africa. - Bennett, Jane (CODESRIA, 2017)
This collection comprises a diverse and stimulating collection of essays on questions of gender and sexualities, crafted by both established and younger researchers. The collection includes fascinating insights into topics as varied as the popularity of thong underwear in urban Kenya, the complexity of Tanzanian youth's negotiation of HIV-cultures, the dialogues between religion and controversial questions in sexualities activism, and the meaning of living as a Zimbabwean girl, who became HIV-positive because her mother had no access to antiretroviral drugs during pregnancy. Some pieces deepen contemporary debates, others initiate new questions. The collection seeks to sustain and invigorate research, policy-making and continentally-focused thought on difficult, yet compelling, realities.